Joint scheduling of AGVs and parallel machines in an automated electrode foil production factory - Tian, Mengxi; Sang, Hongyan; Zou, Wenqiang; Wang, Yuting; Miao, Mingpeng; Meng, Leilei (Expert systems with applications, 2024)
In recent years, the automated guided vehicle (AGV) scheduling problem and parallel machine scheduling problem (PMSP) in workshops have become two hot topics in the field of operational research. In practical production, the two problems are closely related and coupled, and both play important roles in manufacturing systems. However, in the literature, the two problems are often addressed separately, which decreases the efficiency of manufacturing systems to a great degree. Therefore, this paper studies the joint scheduling problem of AGV and parallel machines in a production process of automatic electrode foil. Taking makespan as the optimization objective, a mixed-integer linear programming model is established and verified by the GUROBI solver. A discrete gray wolf optimization algorithm is proposed to solve the AGV-PMSP. An improved NEH heuristic is used to propose the quality of the initial solution. Six neighborhood operators are used to improve the exploration capabilities of the proposed algorithm. A theorem is proved to improve computational efficiency. The performance of the proposed algorithm is verified using comprehensive simulation experiments.